Above-ground carbon stock at Kamojang Regions, West Java, Indonesia - DWIKI DANANG KUNCORO; TEGUH HUSODO; JOKO KUSMORO; RANDI HENDRAWAN; SUROSO; FEMI AFRIYANTI; ERRI NOVIAR MEGANTARA (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Kuncoro DD, Husodo T, Kusmoro J, Hendrawan R, Suroso, Afriyanti F, Megantara EN. 2020. Above-ground carbon stock at Kamojang Regions, West Java, Indonesia. Biodiversitas 21: 1749-1754. Kamojang is one of the regions that have the potential for carbon dioxide (CO2) sequestration and carbon storage for the southern side of West Java Province, Indonesia. The existence of vegetation as a provider of ecological services in the form of carbon dioxide (CO2) absorption and carbon storage certainly has a very important role, either in living conditions (biomass) or dead conditions (necromass). The aims of this study are to determine the total amount of above-ground carbon stock and determine the type of land-use that has the greatest carbon storage potential in the Kamojang region. Data collection in this research combines destructive and non-destructive methods. The measurement of biomass was carried out by the non-destructive sampling method for the category of sapling, poles, trees and necromass and the destructive sampling method for the category of undergrowth and litter. The results showed total above-ground carbon stored in Kamojang area is 4,995.75 t C with the largest potential value of carbon stock in the pine production forest of 163.79 t C/ha.